Risk Factors of Complication from Hip Fracture Surgery in Nan Hospital - Tadee, Sahapap (Journal of The Department of Medical Services, 2024)
Background: Nowadays operative treatment is the main treatment of fragility hip fracture. But in elderly people are usually osteoporotic and they have multiple comorbidities are high risks of postoperative complications. It is important to identify risk factors for incidence and complications after hip fracture surgery to improve outcomes and postoperative functioning in daily life. Objective: To study incidence rate, type of complications and their risk factors after hip fracture surgery. Method: This retrospective cohort study included consecutive patients who sustained fragility hip fracture and underwent operation at Nan Hospital relevant to the period between January 1st, 2020 to December 31st, 2022. The inclusion criteria were those who aged >50 years old, received operative treatment for hip fracture including neck, intertrochanteric, or subtrochanteric femoral fractures and were admitted to this hospital in the study period. Patients who were sustained hip fractures due to pathologic fracture and incomplete or missing data were excluded from this study. Result: From 698 patients were men 176 and women 522 and mean age of 80 years. The incidence of at 1 least complication was 27.4%, the risk factors were BMI <20 kg/m2 and male sex. At least two complication was 2.3%, the risk factors were age >80 years, male, fever unknown origin and coagulopathy before surgery. Conclusion: Patients with BMI < 20 kg/m2 and male sex were associated with 1 or more types of complications from post-operative hip fracture surgery that increased the risks by 1.6 and 2.9 times respectively. Patients aged >80 years, male, have fever unknown origin and have coagulopathy before surgery were associated with 2 or more types of complications that increased the risks by 5.2, 3.3, 6.8 and 32.7 times respectively